Effect of Bi-B-Si-Zn-Al glass additive on the properties of low-temperature sintered silicon carbide ceramics - Zhang, Lan; Yang, Shuquan; Xiao, Meihui; Chen, Lin; Sun, Jun; Ding, Jianjun; Li, Xiaoxiao; Gong, Yi; Zheng, Kang; Zhang, Xian; Tian, Xingyou (Frontiers in Physics, 2023)
To improve the heat dissipation performance of low-temperature co-fired ceramic (LTCC) substrate, we employ Bi-B-Si-Zn-Al glass as the sintering additive to obtain SiC-BBSZA composite ceramic by vacuum hot-press sintering. For investigating the influence of sintering temperature on the structure and properties of the composites, the sintering temperatures were set between 700°C and 1000°C. The results show that different sintering temperatures can lead to the variation of crystal and microstructure, and further affect the properties. The SiC-BBSZA composite ceramic display the preferable comprehensive properties when sintered at 900°C for 2h, with the relative density, thermal conductivity, dielectric constant and Vickers hardness of 95.5%, 8.660 Wm-1K-1, 32.9(20HZ) and 330HV, respectively.